Pengaruh Teknologi Digital Terhadap Pemahaman Generasi Z Tentang Pancasila - Aura Fisqiyah Rahmadillah; Muhammad Aryawinata Sanusi; Nice Electra; Herli Antoni (Pusat Riset dan Inovasi Nasional, 2025)
The digital era brings challenges to the internalization of Pancasila values, especially among generation Z who are exposed to global information flows and foreign cultures. This research aims to analyze the influence of digital technology on the understanding of Generation Z about Pancasila, especially the third precept,